Estudo das propriedades psicométricas da escala WHOQOLold em idosos da região Nordeste - Leão, Isis Simões (2012)
The population aging process increases the number of elderly people worldwide. In Brazil, a country of continental size, this process began in the 40s and happens with specific features in each of the different region s realities. This way, this thesis aimed to evaluate the psychometric properties of a elderly s quality of life (QOL) scale, the WHOQOL-old, in a population of the Northeast of Brazil. We sought to investigate the congruence between the content covered by the scale and the ones deemed as relevant by the participants. It aimed also study the validity evidences of the instrument s internal structure. To achieve the research objectives we adopted the design of multiple methods. The research was organized in two studies. For data collection, both studies used a sociodemographic questionnaire to obtain a profile of the participants and the Mini Mental State Exam (MMSE), used as exclusion criterion. A number of 18 elderly residents of the cities of Natal-RN and Campina Grande-PB, mean age of 73.3 years (SD = 5.9) took part od the study, They were organized into three focal groups (FG) in witch they discussed about the concept of QOL, what enhance and what hinders QOL. For Study II, a quantitative approach, 335 elderly from Campina Grande responded scale WHOQOL-old. They are between 65 and 99 years (M = 74.17, SD = 6.5). The FG data were analyzed by categorical thematic content. For the data analysis of the WHOQOL-old scale were used exploratory factor analysis and calculation of the Akaike and Bayesian information criteria. The results of both studies were triangulated. According to the discussions in the FG, health and social participation have central roles in quality of life. Social participation is related to all the other QOL s influences raised. The participants indicated the relevance of religiosity and were divided about the importance of sexual activity. Exploratory factor analysis (EFA) extracted a model of six factors. Two items (OLD_3 and OLD_9), not loaded on any factor and were excluded. The other items had factor loadings > 0.3. The response categories were reduced from five to three. After the scale changes, the empirical model showed better fit (-2loglikelihood = 8993.90, BIC and AIC = 9183.90 = 9546.24) than the theoretical model (-2loglikelihood = 18390.88, AIC = 18678.88 and BIC = 19228.11). Despite the best information criterion values, the RMESA remained above the ideal (0.06). We conclude that the WHOQOL-old presents psychometric parameters below the ideal when used with the Northeast population, but the improvements made the scale s use acceptable. The WHOQOL-old uses observable variables that matches with the participants' perceptions on quality of life. However, new strategies must be tested for a better sacale refinement